Organization of accounting at budgetary institutions - Koroshchenko, M. (NAU, 2021)
Accounting occupies an important place in the management system of the enterprise, institution, organization, as it collects, measures, registers, processes and transmits information on the processes of production, distribution, exchange and consumption of enterprise resources. This information, on the one hand, is a consequence of enterprise activities, and, on the other hand, is analyzed to make optimal management decisions in order to carry out economic activities under market conditions. In this case, accounting requires proper organization, because the effective organization of accounting involves the creation of a flexible, optimal and multifunctional system focused on providing source accounting information to users.
Keywords: accounting; management; system of the enterprise; organization; registers; information